A feeding guild indicator to assess environmental change impacts on marine ecosystem structure and functioning. Issue 9 (28th June 2020) - Thompson, Murray S. A.; Pontalier, Hugo; Spence, Michael A.; Pinnegar, John K.; Greenstreet, Simon P. R.; Moriarty, Meadhbh; Hélaouët, Pierre; Lynam, Christopher P.
Abstract: Integrating food web indicators into ecological status assessments is central to developing effective management measures that can improve degraded ecosystems. This is because they can reveal how ecosystems respond to environmental change that cannot be inferred from studying habitat, species or assemblages alone. However, the substantial investment required to monitor food webs (e.g. via stomach contents analysis) and the lack of internationally agreed approaches to assessing them has hampered their development. Inventories of trophic interactions have been collated world‐wide and across biomes, and can be applied to infer food web structure and energy flow. Here, we compile a new marine dataset containing 8, 092 unique predator–prey interactions from 415, 294 fish stomachs. We demonstrate how feeding guilds (i.e. groupings based on diet and life stage) could be defined systematically and in a way that is conducive to their application internationally across ecosystems; and apply them to the North Sea fish assemblage to demonstrate their responsiveness to anthropogenic pressures. We found evidence for seven distinct feeding guilds. Differences between guilds were related to predator size, which positively correlated with piscivory, phylogeny, with multiple size classes of a species often in the same guild, and habitat, as pelagic, benthic and shallow‐coastal foraging was apparent. Guild biomasses were largely consistent through time at the North Sea‐level and spatially aggregated at the regional level with change relating to changes in resource availability, temperature, fishing and the biomass of other guilds. This suggests that fish biomass was partitioned across broad feeding and environmental niches, and changes over time were governed partly by guild carrying capacities, but also by a combination of covariates with contrasting patterns of change. Management of the North Sea ecosystem could therefore be adaptive and focused towards specific guilds and pressures in a given area. Synthesis and applications . We propose a food web indicator which has been explicitly called for to inform policy via food web status assessment as part of the European Union's Marine Strategy Framework Directive and the indicator toolkit supporting The Convention for the Protection of the Marine Environment of the North‐East Atlantic (the 'OSPAR Convention'). Abstract : We propose a food web indicator which has been explicitly called for to inform policy via food web status assessment as part of the European Union's Marine Strategy Framework Directive and the indicator toolkit supporting The Convention for the Protection of the Marine Environment of the North‐East Atlantic (the 'OSPAR Convention'). Résumé: L'intégration des indicateurs de réseaux trophiques dans les évaluations des statuts écologiques est essentielle pour développer des mesures de gestions efficaces des écosystèmes dégradés. De par leur nature intégrative, ces indicateurs peuvent dévoiler la façon dont les écosystèmes répondent aux changements environnementaux même lorsque ces réponses ne peuvent être déduites des études d'habitats, d'espèces ou d'assemblages effectuées séparément. Cependant l'investissement considérable nécessaire à la surveillance des réseaux trophiques (par ex. les analyses de contenus stomacaux) et l'absence d'une approche internationalement acceptée pour les évaluer a freiné leur développement. Les interactions trophiques ont été inventoriées à travers le monde et les biomes et peuvent être utilisés pour en déduire la structure des réseaux trophiques et les flux d'énergie. Nous avons compilé un nouveau jeu de données marines contenant 8 092 interactions uniques proie‐prédateur à partir de 415 294 estomacs de poissons. Nous décrivons une manière de caractériser systématiquement les guildes alimentaires (ie. regroupement basé sur le régime alimentaire et le moment de la vie) et de manière propice à leur application dans tous les écosystèmes à l'échelle internationale; et nous les mettons en œuvre dans les assemblages des espèces de poissons de la Mer du Nord pour décrire leur réactivité aux pressions anthropogéniques. Nous avons mis en évidence sept guildes alimentaires distinctes. Les différences entre guildes sont liées à la taille des prédateurs (positivement corrélée avec la piscivorie), la phylogénie (plusieurs classes de taille d'une espèce sont souvent dans la même guilde), et l'habitat (les habitats pélagiques, benthiques et côtier peu profond sont mis en évidence). Les biomasses des guildes sont essentiellement constantes à travers le temps à l'échelle de la Mer du Nord et agrégées spatialement à l'échelle régionale. Les fluctuations des biomasses sont dictées par la variation de la disponibilité alimentaire, la température, la pêche et la biomasse des autres guildes. Cela suggère que la biomasse des poissons est divisée entre de larges niches alimentaires et environnementales et que les changements temporels sont en partie contrôlés par la capacité de charge des guildes mais aussi par une combinaison de covariables aux fluctuations opposées. La gestion des écosystèmes dans la Mer du Nord pourrait ainsi être adaptatif et se concentrer sur des pressions et guildes spécifiques dans une région donnée. Synthèse et applications . Dans le cadre de la Directive Cadre Stratégie pour le Milieu Marin de l'Union Européenne, nous proposons un indicateur des réseaux trophiques, ouvertement réclamé pour éclairer les pratiques, via l'évaluation des statuts des réseaux trophiques, ainsi que la boite à outils de l'indicateur en appui à la Convention pour la protection du milieu marin de l'Atlantique du Nord‐Est (Convention OSPAR).